Kesan Pelarut Terhadap Pemalar Optik Lamtan Organik Laser Dye - Mat Yunus, W. Mahmood; Man, Zulkifly (Universiti Putra Malaysia Press, 1997)
The optical constants n and k of R6G and Fluorscein in methanol and ethanol (at a particular concentration of 5 X 10-5 molar) as a function of wavelength are reported. The extinction coefficient k and the refractive index n were measured in the range of wavelength 200-700 nm and 540-700 nm respectively. The results showed that the refractive index n obtained for R6G and Fluorescein in ethanol was significantly higher than in methanol.